Intercellular Adhesion Molecule-1 (ICAM-1) and ICAM-2 Differentially Contribute to Peripheral Activation and CNS Entry of Autoaggressive Th1 and Th17 Cells in Experimental Autoimmune Encephalomyelitis - Haghayegh Jahromi, Neda; Marchetti, Luca; Moalli, Federica; Duc, Donovan; Basso, Camilla; Tardent, Heidi; Kaba, Elisa; Deutsch, Urban; Pot, Caroline; Sallusto, Federica; Stein, Jens V.; Engelhardt, Britta (Frontiers in Immunology, 2020)
In experimental autoimmune encephalomyelitis (EAE), an animal model of multiple sclerosis (MS), myelin-specific T cells are activated in the periphery and differentiate in T helper (Th) 1 and Th17 effector cells, which cross the blood-brain barrier (BBB) to reach the central nervous system (CNS), where they induce neuroinflammation. Here, we explored the role of intercellular adhesion molecule-1 (ICAM-1) and ICAM-2 in the activation of naïve myelin-specific T cells and in the subsequent migration of differentiated encephalitogenic Th1 and Th17 cells across the BBB in vitro and in vivo. While on antigen-presenting cells ICAM-1, but not ICAM-2 was required for the activation of naïve CD4+ T cells, endothelial ICAM-1 and ICAM-2 mediated both Th1 and Th17 cell migration across the BBB. ICAM-1/-2-deficient mice developed ameliorated typical and atypical EAE transferred by encephalitogenic Th1 and Th17 cells, respectively. Our study underscores important yet cell-specific contributions for ICAM-1 and ICAM-2 in EAE pathogenesis.